Comfort Filters in a Total Energy Demand Optimization Method for the Passive Design of a Building. (December 2015) - Ferrara, Maria; Sirombo, Elisa; Fabrizio, Enrico; Filippi, Marco
Abstract: The effective design of sustainable buildings results from an accurate optimization process of all the interrelated variables. The authors developed a replicable methodology for the optimization of the building envelope design. Following a previous work, where in the pre-processing and the optimization phases the minimization of the total energy demand is performed by coupling TRNSYS ® with GenOpt ®, this paper is focused on the post-processing phase of the methodology, in which the results are validated and the comfort filters are applied. As an explanatory example, the application of the methodology to a school classroom located in two different climates is presented.